Classification in Para skiing: do better performing skiers have better visual functions? - Stalin, A.; Dalton, K. (Frontiers in Sports and Active Living, 2023)
Introduction: Currently, Paralympic skiers with vision impairment are allocated to classes based only on their better eye static visual acuity and visual field diameter. These studies were conducted to investigate whether a broad range of visual functions were different among groups of skiers with different levels of skiing performance.